The effect of corporate social responsibility towards consumer buying behaviour: a study among universities students / Bibianah Thomas and Nor Suziwana Tahir - Thomas, Bibianah; Tahir, Nor Suziwana (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
Business corporations need to realize that in order to achieve their primary objective, they need to consider their responsibility towards society and environment. However, there are still a lot of unethical businesses that ignore their stakeholder’s interest. Therefore, business need to aware that their involvement of CSR practices in certain extent does affect the consumer buying behavior. This paper examines the relationship between CSR practices and consumer buying behavior. Quantitative approach was employed and 241questionnaires were collected and valid to be used. It was found that positive relationship existed between all the CSR practices (economic, legal, ethical, and philanthropic) and the consumer buying behavior. However, based on the students in Selangor perspective, the main element of CSR practices that influence the consumer buying behavior is economic. Therefore, business corporations need to strive to maximize their shareholder’s wealth as the consumers expect the corporations to fulfill the shareholder’s interest as they are among those who contribute in providing funds for the businesses survival and growth. Additionally, consumers also expect the business corporations should offer reasonable price and provide a good quality of products and services to them.